Perlindungan Hukum Pedagang Kecil dari Keberadaan Franchise Minimarket (Studi Peraturan Walikota Bandar Lampung Nomor 17 Tahun 2009) - Rissa Afni Martinouva (Universitas Bandar Lampung (UBL), 2017)
Small traders owned and managed by entrepreneurs who have capital to lower middle. In the development of small traders, present business activity trade with minimarket franchise formats such as